2008
DOI: 10.1001/archfacial.2007.18
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Imaging of Live Human Keloid and Facial Tissue Using Multiphoton Microscopy

Abstract: The value of imaging living tissue is a significant benefit. Because keloids and hypertrophic scars result from altered collagen metabolism, the development of clinical multiphoton microscopy systems may allow examination of wound healing dynamics in vivo and potentially provides a means to monitor therapy without the need for biopsy or the risk of injury to tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 16 publications
(23 reference statements)
4
39
0
Order By: Relevance
“…Most clinicians rely on clinical observation and palpation of the scar to monitor disease progression, but this is subjective and not quantitative. A wide range of non-invasive tools exist to monitor scars, including laser Doppler, ultrasonography, tonometry, two-photon excited fluorescence and second harmonic generation, and multiphoton microscopy [12][13][14][15]. However, the high instrument cost, the lack of objective procedures, or long duration measurements impede the wide application of these instruments in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Most clinicians rely on clinical observation and palpation of the scar to monitor disease progression, but this is subjective and not quantitative. A wide range of non-invasive tools exist to monitor scars, including laser Doppler, ultrasonography, tonometry, two-photon excited fluorescence and second harmonic generation, and multiphoton microscopy [12][13][14][15]. However, the high instrument cost, the lack of objective procedures, or long duration measurements impede the wide application of these instruments in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen fibers produce a high SHG signal [18] and can be imaged inside skin dermis with SHG microscopy [4,18]. Recently, SHG was also used for investigating collagen-fiber orientation and their structural changes in fibrotic collagen [19], human dermis [20][21][22][23], keloid [24], cornea [25,26] and in the tumor microenvironment [27][28][29][30]. The combination of TPEF and SHG is particularly useful when imaging dermis tissue because the two main components of dermis (collagen and elastin) can be imaged with SHG and TPEF microscopy, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Recently, SHG and TPEF based imaging techniques have been used to study the ECM structure of normal and keloid skin ex vivo; the structure and the volume concentration of collagen and elastin were found to be distinct between normal and keloid skin. [10][11][12] The multi-photon microscopy has been used for in vivo and ex vivo collagen and elastin quantification, and it has been suggested that the multi-photon microscopy could be a potential tool for in vivo keloid and scar diagnosis. [10][11][12][13] However, the long measurement time, the relatively high overall system cost, and the lack of ability to quantify skin redness are the limiting factors for widely adopting the multi-photon-based techniques in the clinical setting for investigating keloid disease.…”
Section: Introductionmentioning
confidence: 99%